Growth and survival of Brazil nuts (Bertholletia excelsa Bonpl.), in different environmental conditions in region River Trombetas, Oriximiná, Pará, Brazil - Scoles, Ricardo; Gribel, Rogério; Klein, Gilmar Nicolau (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
This study examines the growth and survival of Brazil nut tree (Bertholletia excelsa, Lecythidaceae) in different environmental conditions within experimental plantations in the Trombetas River valley. One hundred and forty four saplings were planted in a random block design, with three natural light treatments: manioc field (100% canopy removal), young secondary forest (20-80% canopy cover) and the understory of a Brazil nut plantation (< 10% canopy opening). Every two months for a period of two years plant height and stem diameter were measured, and mortality and regrowth were noted. There were significant differences in the performance of Brazil nut saplings between treatments, with the most marked differences being at the highest level of luminosity (manioc field). The open field saplings grew in height 13 times more than those planted in secondary forest, and nearly 30 times more those in the understory of the plantation area. The open field saplings exhibited a growth in diameter 4.4 times greater than saplings planted in secondary forest and 7.7 times greater than saplings planted in the understory. Regardless of the light treatment, the Brazil nut saplings had high survival rate and exhibited strong regrowth following stem damage. Overall we report that Brazil nut saplings perform better in full daylight conditions such as abandoned crop fields and forest gap. In enrichment or reforestation plantings, vegetation around Brazil nut plants should be cleaned frequently to avoid over-shading the crown and to guarantee high growth rates.
Keywords: Bertholletia excelsa; Brazil nut; Survival; Crown tree; Enrichments plantings; Canopy gap